OP0213 Rituximab Versus Azathioprine for Maintenance in Antineutrophil Cytoplasmic Antibodies (ANCA)-Associated Vasculitis (MAINRITSAN): Follow Up at 34 Months. (23rd January 2014) - Terrier, B.; Pagnoux, C.; Karras, A.; Khouatra, C.; Aumaitre, O.; Cohen, P.; Maurier, F.; Decaux, O.; Demurs-Clavel, H.; Gobert, P.; Quemeneur, T.; Godmer, P.; et al.
Abstract : Background: The prospective, randomized, controlled MAINRITSAN trial compared rituximab (RTX) to azathioprine (AZA) to maintain ANCA-associated vasculitis (AAV) remission. Once remission was obtained with a conventional regimen, patients were randomly assigned to receive a 500-mg RTX infusion on D1, D15, 5.5 months later, then every 6 months for a total of 5 infusions over 18 months, or AZA for 22 months at the initial dose of 2 mg/kg/d. The primary endpoint was the major relapse rate (EULAR/ACR criteria) at 28 months. This study demonstrated that 500 mg of rituximab (RTX) every 6 months was superior to azathioprine (AZA) to maintain ANCA-associated vasculitis (AAV) remission during the 28-month follow-up, with a similar profile of tolerance. Objectives: This study describes the extended follow-up of patients included in the MAINRITSAN trial. Methods: Extended follow-up was ascertained from the patients included in the trial. Data on relapse and survival were collected from physician records. All patients were analyzed according to the group to which they were randomized. Results: Median duration of follow-up was 34.3 months (IQR, 28.7-39.6 months). Six out of 56 (10.7%) RTX patients and 24/53 (45.3%) AZA patients had at least one major relapse. The risk of major relapse remained significantly lower in the RTX-arm compared to the AZA-arm (hazard ratio 0.18, 95% CI 0.09 to 0.42, P<0.0001). During follow-up, 4 patients died in the AZA arm but none in the RTX arm. Overall survival rates was lower in the RTX-arm compared to the AZA-arm (P=0.037). Conclusions: Despite relapses in the RTX-arm after the end of the study period, RTX remains associated with a lower risk of relapse than AZA. RTX is also associated with a better overall survival compared to AZA. Disclosure of Interest: None Declared